Features of Anatomy of the Greater Omentum - Nurov Jamshid Raxmatovich; Ahmadova Maftuna Amin qizi (International Journal on Orange Technologies, 2021)
The article has studied in detail the macro and microscopic anatomy of the greater omentum of a person. Variants, morphological, histotopographic features and ligament apparatus of the greater omentum are indicated. The obtained data are useful for surgical, including laparoscopic, interventions on the abdominal or¬gans. The conducted studies complement the changes in histotopographic relationships of the glands, lymphatic bed, and lymphoid structures described in the literature. The data in perspective can be used for the correction of ongoing conservative and operational activities.